South Rings in Panorama '87 - Unknown (Daily Express)
Panorama 1987 is here and the sweet sound of steel will emanate from Skinner Park, San Fernando, as the Pan-Round-Neck and South/Central Zonal preliminaries begin. The judges for the competition are listed.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago